آليات تسوية منازعات الأعمال التحضيرية للانتخابات التشريعية في ضوء مستجدات أحكام الأمر 21-01 المتضمن القانون العضوي المتعلق بنظام الانتخابات الجزائري - جوادي, الياس; يعيش تمام, شوقي (University of Eloued جامعة الوادي, 2021)
سبق كل انتخابات تشريعية عملية تحضيرية أو تمهيدية لها، وهي مجموعة من الإجراءات الأساسية أقرها المشرع في نظام الانتخابات ضمن الباب الثاني من الأمر 21-01، حيث أنه لا يمكن إجراء المرحلة الثانية من العملية الانتخابية إلا بعد استكمال جميع الإجراءات المتعلقة بعمليات التسجيل ومراجعة القوائم الانتخابية وشروط الترشح، فهي مرتبطة بالعمليات التي تعقبها (الانتخاب وإعلان النتائج)، ومن بين العمليات التحضيرية أو الإجراءات التمهيدية لأي عملية انتخابية والتي نحن بصدد دراستها، هي تنظيم وإعداد القوائم الانتخابية وفتح باب الترشيحات ومطابقته مع الشروط المطلوبة في المترشح، وقد أتاح نظام الانتخابات للناخب والمترشح الطعن في قرارات الهيئات المختصة خلال هذه المرحلة التحضيرية أمام الجهات الادارية والقضائية المختصة، وذلك من أجل ضمان سلامة العملية الانتخابية وإضفاء طابع الشفافية Abstract: Each legislative election is preceded by a preparatory or preparatory process for it, which is a set of basic procedures approved by the legislator in the election system under Chapter Two of Ordinance 01- 21, as the second phase of the electoral process can only be conducted after completing all the procedures related to the registration processes and reviewing the electoral lists. And the conditions for candidacy, as they are related to the processes that follow it (election and announcement of results , Among the preparatory processes or preparatory procedures for any electoral process that we are about to study are the organization and preparation of electoral lists, opening the door for nominations and their conformity with the conditions required for the candidate, and the election system has allowed the voter and candidate to challenge the decisions of the competent bodies during this preparatory phase before the competent administrative and judicial authorities. This is in order to ensure the integrity of the electoral process and impart a character of transparency
Mechanisms for the settlement of disputes in connection with the preparations for legislative elections, in the light of the updated provisions of Ordinance No. 21-01 on the Algerian electoral system
مقال
Keywords: منازعات – الأعمال التحضيرية – الانتخابات التشريعية – نظام الانتخابات- القيد الانتخابي – منازعات الترشح.; Disputes, preparations, legislative elections, electoral registration, election disputes.